The association between anemia and urinary tract infection among the pregnant women in Baghdad - Jabba, Areej- A. (Journal of the Faculty of Medicine Baghdad, 2006)
Background: Severe anaemia predisposes to infection particularly during pregnancy especially reproductive tract and urinary tract infection .Iron deficiency anemia is an important publichealth problem which contributes to morbidity and mortality in pregnant women, even milder anemia can cause urinary tract infection .Methods: This study was carried out during February to May 2005 among 200 pregnant women during their routine visits to the maternal and child health centers in different parts of Baghdad city , they were inquired carefully about their ages parity , their gestational age and examined physically in addition to testing their blood for lib concentration and urine for presence of bacteruria. The sample was devided into two groups: The first group had confirmed diagnosis with UTI (100) , the second normal group (100) considered as a control. Results : The highest percentage of Urinary tract infected pregnants in the sample were nuillipara 44% and those in the second trimester showed highest percentage 57% of the sample . the mean blood 1 Ib was significantly lower in UTI cases (10.5 g/dl). the anemic individuals (